Characteristics of the drinking habits of people who overdose over‐the‐counter drugs: Insights from a nationwide Japanese survey - Satomi Mizuno; Satoshi Inoura; Toshihiko Matsumoto; Takuya Shimane (PCN Reports)
Abstract Aim To analyze the drinking habits of individuals who overdosed on over‐the‐counter (OTC) drugs, such as cough suppressants, antitussives, antipyretic analgesics, and combination cold medications, in Japan. Methods This cross‐sectional study analyzed data collected from 2881 participants through a national survey conducted in Japan in 2023. Through a self‐administered questionnaire, the participants were categorized into OTC (overdosed OTC drugs in the past year) and control (did not overdose OTC drugs) groups. Variables related to drinking habits, social background, smoking habits, use of other medications, such as analgesics, tranquilizers, controlled drugs, and products containing high concentrations of caffeine, and perception of OTC drugs were compared between the two groups. Additionally, we matched the participants in the OTC (n = 25) and control (n = 100) groups by sex and age in a 1:4 ratio to assess these variables. Multivariate analyses were performed to examine how these factors are associated with drinking habits in individuals with OTC drug overdose. Results OTC drug overdose was prevalent among teenagers and those in their 50s, and was associated with habitual binge drinking and consumption of energy drinks. Those overdosing on OTC drugs obtained them mostly from drugstores and pharmacies. Conclusion This is the first study to show a relationship between drinking habits and OTC drug overdose. An understanding of the characteristics of drinking habits in those who overdose on OTC drugs can help reduce fatal health risks in this population.